THE IMPACT OF TRAINING AND CAREER DEVELOPMENT, INFORMATION SHARING AND DIVERSITY ON DEVELOPING A SUSTAINABLE SUPPLY CHAIN STRATEGY - Kongtana, Jakkrapun; Khasasin, Rungarun; Khasasin, Kairung; Nualkaw, Suwat (International Journal of Supply Chain Management, 2020)
Abstract- The prime objective of the present study is to explore the impact of diversity management, information sharing and Training and career development on sustainability of the organization. moreover, mediation role of Supply chain management strategy is examined as well. It is very important for the organizations to develop competitive advantage. For this reason, The questionnaire were distributed among the employees of banks of Indonesia. The response rate of the current study is 53.45 percent. This study chose the Partial least squares structural equation modeling (PLS-SEM) for analyzing the collected data. All of the proposed relationships were found significant. Present study is important for the policy makers of banking sector to focus on their human resource to gain competitive advantage and sustainability.